Informal Employment Trends in Nepal - Neupane, Ramesh (Nepalese Journal of Development and Rural Studies, 2023)
The paper assessed both formal and informal employment trends based on panel data (1991-2022) estimated by ILO model. Various forms of employments (e.g., labour force participation, employment to population ratio, unemployment, wage and salaried workers, self-employed workers, contributing family workers, vulnerable employment and employment by economic classes, and contribution of informal economy to GDP) are presented and discussed statistically. Over the years, level of poverty is declined considerably. Indirect techniques such as MIMIC and DGE models were used to estimate the proportion of informal economy to GDP, suggesting Nepal is in the second position after Sri Lanka among the South Asian countries.